Enhancing Carbon Monoxide Oxidation of Cobalt-Nickel Containing A-Deficient Perovskites through Exsolution Agents and Reduction-Oxidation Pretreatment - Liang, Lew Guo; Ramli, Wan Khairunnisa Wan; Ibrahim, Naimah; Abdullah, Sureena (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2025)
In this work, different types of exsolution agents and pretreatment processes, comprising reduction-oxidation (RO) components, were introduced to modulate the exsolution process of A-deficient perovskites, La0.7Ce0.1Co0.3Ni0.1Ti0.6O3. The catalysts were assessed using field emission scanning electron microscopy with energy dispersive spectroscopy (FESEM/EDS), X-ray Diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). Their carbon monoxide (CO) oxidation activity was also compared. The results showed that the catalytic activity degraded at 520 °C when hydrogen (E-H) was used as the exsolution agent. When RO components were introduced as exsolution agents (E-CO/O2) or in the pretreatment (RO2% and RO18%), the deactivation at high temperatures was mitigated. The results of this study showed that RO18% was favourably pretreated with RO components, recording the highest CO conversion of 60.57% at 520 °C and across all temperatures with no degradation at high temperature. It also recorded the lowest activation energy of 14.449 kJ/mol. The EDS, XRD, and XPS analyses of the catalyst demonstrated that the active sites for this reaction are primarily Co2+ with Ni serving as the anchor between the metals and perovskites support. A high amount of lattice oxygen (O2) with higher binding energy and chemisorbed O2 species also influenced the improved catalytic activity, attracting CO for reaction, reacting with the available surface O2 and the faster replenishment of O2 vacancies by the absorbed and bulk O2 lattice. These findings highlight the prospects of CO and O2 inclusion in pretreatment for perovskite catalyst as options to reduce metal agglomeration and further improve CO oxidation activity. Copyright © 2025 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).